Efektivitas Asistensi Mengajar dalam Menigkatkan Kualitas dalam Pembelajaran di SDN 1 Aikmel Utara 2024 - Zulfadli Hamdi; Muhammad Mirwan Apriandi; Enki Rizaldo; Sapma Dewi Anggraini; Lilik Suriani; Baiq Risa Apriantari; Maeli Astuti (Alpatih Harapan Semesta, 2025)
Teaching assistance is a strategic program to increase the effectiveness of the learning process through assistance in the classroom. This research aims to analyze the role of teaching assistants, their impact on student learning, and the challenges faced in implementing the program at SDN 1 Aikmel Utara. The research used a qualitative descriptive method with a case study approach, involving teachers, teaching assistants and students as the main informants. Data collection techniques include direct observation, semi-structured interviews, and document analysis. The research results show that teaching assistants play a significant role in supporting classroom management, guiding students who need additional help, and creating an interactive learning atmosphere.